2021
DOI: 10.1007/s10864-021-09434-5
|View full text |Cite
|
Sign up to set email alerts
|

Using Interteaching to Promote Online Learning Outcomes

Abstract: Due to the COVID-19 pandemic, educators have been forced to rapidly transition away from in-person learning environments to completely online formats. Many of these educators have had little or no training and experience teaching online, contributing to stress and anxiety. To compound this problem even further, there are a multitude of online learning technologies from which to choose that can be relatively costly and require an intensive production process. In an effort to provide immediate relief to those de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis by Hurtado-Parrado et al (2022) showed that fewer than 25% of studies included more than five of the seven originally outlined components. For example, pair discussions have sometimes been replaced with small-group discussions (Goto & Schneider, 2010), quality points have not always been used (Saville et al, 2012) or have been further emphasized and enhanced (Rosales et al, 2014), group discussions have been held online (Krebs et al, 2021), and interteaching has been used in larger courses with class times exceeding 1 hr (Scoboria & Pascual-Leone, 2009). These deviations, however, have not changed the comparative success of interteaching as an instructional method (Filipiak et al, 2010).…”
mentioning
confidence: 99%
“…A recent meta-analysis by Hurtado-Parrado et al (2022) showed that fewer than 25% of studies included more than five of the seven originally outlined components. For example, pair discussions have sometimes been replaced with small-group discussions (Goto & Schneider, 2010), quality points have not always been used (Saville et al, 2012) or have been further emphasized and enhanced (Rosales et al, 2014), group discussions have been held online (Krebs et al, 2021), and interteaching has been used in larger courses with class times exceeding 1 hr (Scoboria & Pascual-Leone, 2009). These deviations, however, have not changed the comparative success of interteaching as an instructional method (Filipiak et al, 2010).…”
mentioning
confidence: 99%